Pemetaan Tantangan Lembaga Pendidikan HKBP Berdasarkan Teori Jobs to be Done - Binsar Jonathan Pakpahan (Universitas Kristen Satya Wacana, 2023)
This article explains the challenges of Protestant Christian Batak Church (Huria Kristen Batak Protestan – HKBP) educational institutions, especially those managed by the Protestant Batak Christian Huria Education Board (BPP-HKBP). The research aims to solve the problems of mapping HKBP primary and secondary educational institutions. By using the method of field research and school data, assisted by systems thinking theory analysis, the internal problems found in HKBP educational institutions are no longer one. Still, they are already in the form of a circle: a lousy reputation reduces the number of students making schools financially weak and lacking adequate human resources and infrastructure, which brought the importance even less. The way to break the deadlock is to find a way to strengthen the reputation in the form of branding new values. The Jobs to be Done theory helps this research see that the new value proposal must be based on the needs of prospective users of different generations. The result is that the study finds that the branding theme centered on values ​​and character is the best solution to improve the image of HKBP educational institutions. This research helps improve the HKBP education institution’s management by mapping the user needs and providing answers to these needs, which could be helpful not only in HKBP but also in other educational institutions.